A one-step chemical vapor deposition approach for solid solution PrxNd1−xB6 nanowire growth. Issue 117 (10th November 2015) - Li, Qidong; Zhao, Yanming; Fan, Qinghua; Han, Wei
Abstract : Structurally uniform and well-doped single crystalline solid solution Pr x Nd1− x B6 nanowires were fabricated by a one-step CVD approach for the first time. Abstract : Dual-rare earth hexaborides Pr x Nd1− x B6 nanowires have been successfully synthesized on silicon substrates by a one-step CVD method at a temperature of 1030 °C. The quasi-aligned nanowires are shown to be structurally uniform and well-doped single crystals based on comprehensive analysis. The present preparation technique is an effective and invaluable method to develop and optimize dual-REB6 nanostructured emitters.